A role for Toll-like receptor 4 in the host response to the lung infection of Yersinia pseudotuberculosis in mice. (February 2016) - Choi, Jin-A; Jeong, Yu-Jin; Kim, Jae-Eun; Kang, Min-Jung; Kim, Jee-Cheon; Oh, Sang-Muk; Lee, Kyung-Bok; Kim, Dong-Hyun; Kim, Dong-Jae; Park, Jong-Hwan
Highlights: Lung infection with Yptb strain IP2777 induces systemic infection in mice. TLR4 protects mice from lethality induced by lung infection with Yptb. TLR deficiency leads to rapid spreading of bacteria into systemic organs. More severe pathology was observed in the liver and spleen of TLR4-deficient mice. Abstract: Although a Yersinia pseudotuberculosis ( Yptb ) lung infection model has been developed to study Y. pestis pathogenesis, it is still necessary to establish a new animal model to mimic the pathophysiological features induced by Y. pestis infection. Here, we provide a new lung infection model using the Yptb strain, IP2777, which displayed rapid spread of bacteria to the liver, spleen, and blood. In addition, we examined whether TLR4 is involved in Yptb -induced pathogenesis in the lung infection model of mice we generated. Following lung infection of WT and TLR4-deficient mice with the Yptb strain IP2777, the survival rate, bacterial colonization, histopathology, and level of cytokines and chemokines in the lung, spleen, liver, and blood were analyzed. TLR4-deficient mice had a lower survival rate than WT mice in response to Yptb lung infection. Although the bacterial colonization and pathology of the lung were comparable between WT and TLR4-deficient mice, those of the spleen and liver were more severe in TLR4-deficient mice. In addition, the levels of TNF-α and CXCL2 in the liver and IL-6 and CXCL2 in the blood were higher in TLR4-deficient mice than in WT mice. Our results demonstrate that TLR4 is necessary for optimal host protection against Yptb lung infection and TLR4-deficient mice may serve as a better genetic model of Yptb infection for mimicking Y. pestis infection.